Colin P. A. Jones / Frank S. Ravitch: The Japanese Legal System - Fisher, James C. (Zeitschrift für Japanisches Recht, 2021)
West Academic Publishing, St. Paul MN, 2018, 441 + 9 pp. (Index), $121.00, $90.75 ebook, ISBN: 9781642425369